DETERMINAN MOTIVASI KERJA SERTA IMPLIKASINYA TERHADAP KINERJA KARYAWAN PADA PT. INNOVATIVE PLASTIC PACKAGING KARAWANG PLANT - Saepudin, Asep (LPPM Universitas Buana Perjuangan Karawang, 2017)
ABSTRACT The problem raised in this research is to know, analyze and review the training, compensation, motivation and performance of employees at PT.Innovative Plastic Packaging Karawang plant. Analyze and prove the effect of training and compensation on motivation partially and simultaneously, analyze and prove the influence of motivation on employee performance. As well as analyzing and proving the effect of training, compensation partially and simultaneously on employee performance through motivation. This study uses path analysis, with the number of samples taken as much as 80 respondents with saturated sampling technique. The research method used in this research by using descriptive method and verifikatif. From the results of analysis of research data obtained some conclusions as follows: (1) Employee performance (Z) is in the range of good scale. Where the indicator of conformity of tasks with work procedures obtained the highest score, while satisfaction on the work obtained the lowest score. (2) Motivation (Y) is in the range of a good scale. Where the peer assistance indicators get the highest score, while the achievement award gets the lowest score. (3) Training (X1) is on a good scale range. Where the cost advantage training indicator scores get the highest score, while the training material indicator scores the lowest. (4) Compensation (X2) is in the range of a good scale. Where employment status indicators get the highest score, while the profit bonus indicator companies get the lowest. (5) Training (X1) have a significant effect on motivation (Y), with t test criterion 2.617> t table 1.991. Compensation (X2) have a significant effect on the motivation with the criterion t test 7.349 > t table 1.991. Training (X1), compensation (X2) simultaneously affect the motivation (Y) with the test criteria F arithmetic 95.20> F table 2.72. (6) Motivation (Y) has a significant effect on employee performance with the test ktiteria t-test 13.349> t-table 1.991. (7) Training (X1) has no significant effect on employee performance (Z) with the criterion of t test count 1,872